Contractual renegotiations and international investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Nijhoff international investment law series, 2020)
"In Contractual Renegotiations and International Investment Arbitration, Aikaterini Florou explores the tangible and sensitive problem of the renegotiation of state contracts, and the relationship between those contracts and the overarching international investment treaties. By bringing novel insights from economics, the author deconstructs and decodes the contract-treaty interaction by showing that it is not only treaties that have an impact on the underlying contracts, but also those contracts have an effect on the way the open-textured treaty standards are interpreted. The originality of the argument is combined with an innovative interpretative methodology based on relational contract theory and transaction cost economics. Departing from the traditional emphasis of international lawyers on the text of investment contracts, the author shows instead that such contracts are first and foremost "economic animals" and the theory of obsolescing bargaining does not paint a full picture of the contract-treaty interaction."